Comparative Evaluation of Production Performance in Improved Chicken Varieties for Backyard Farming - Niranjan, M.; Sharma, R.P.; Rajkumar, U.; Reddy, B.L.N.; Chatterjee, R.N.; Battacharya, T.K. (International Journal of Poultry Science, 2008)
The growth and production performance of 4 chicken varieties developed for backyard farming were evaluated in the present study. The body weights were significantly (p